Measures in Medieval English Recipes – Culinary Vs. Medical - Bator, Magdalena; Sylwanowicz, Marta (Studia Anglica Posnaniensia, 2017)
The present paper deals with an analysis of medieval culinary and medical recipes. A major feature which will be of interest is the use of measure terms. The research has been based on material from 14th and 15th century recipe collections. First, the major weight and measure systems which were used in the Middle English period will be presented. Then, the measure terms used in the analysed texts are collected and categorised into three groups: specific, non-specific, and container-related terms. The study, apart from showing the variety of measure terms used at the time, also compares two types of recipes, i.e., medical and culinary.